Optimal Planning of Standalone Solar-Wind-Diesel Hybrid Energy System for a Coastal Area of Bangladesh - Ahmed Zubair; Aman Abdulla Tanvir; Md. Mehedi Hasan (Institute of Advanced Engineering and Science, 2012)
For sustainable development of a country access to electricity in every moment is now the basic need for the current civilization. Power crisis is one of the major barriers for economic development of Bangladesh. Bangladesh lacks in fossil fuel reservation. Abundance of renewable energy sources in the form of solar energy, wind energy provides opportunities of renewable energy based hybrid energy system in the coastal areas of Bnagladesh. Energy generation by hybrid system reduces the generation cost and will help in balancing the cost of energy. Again a standalone renewable enegy incorporated hybrid energy system will reduce load demand from the grid and will be an eco-friendly energy system. This paper proposed a cost effective design of standalone solar-wind-diesel hybrid power system in a coastal area of Bangladesh. Considering different conditions for a coastal area design and simulation of the hybrid power system was performed. Detailed economic analysis and comparison with solar based and diesel based energy system clearly reveals that proposed hybrid power system was found a cost effective solution for coastal areas of bangladesh.DOI:http://dx.doi.org/10.11591/ijece.v2i6.830